Gender (dis)parity in translations of French and Francophone Authors in Croatia from 1991 to 2020 - Mikšić, Vanda (Anafora, 2024)
The paper analyzes the proportion of French and Francophone female authors in Croatian translations published as volumes between 1991 and 2020. Quantitative analysis is carried out on the basis of the relational database of bibliographic units created as part of the University of Zadar institutional project Sociological and translational aspects of the reception of French and Francophone literature in Croatia after 1991 (IP.01.2021.15). Bearing in mind that literary translation is a cultural and communicative, therefore linguistic and social, historical, but also political practice (Toury, 249), and relying, from the theoretical point of view, on translation studies, literary theory, sociology (of translation, literature, gender) and feminist theories, my goal is to answer the following research questions: what is the ratio of female and male authors of French and Francophone literature in the translations published in Croatia in the thirty-year period (in total and by decade), has this ratio changed in relation to the previously researched period from 1945 to 1985 (Dragojević and Cacan), and how this ratio corresponds to: a) the presence and visibility of the French and Francophone female authors in France, where the majority of translated works have originally been published, b) the situation of French and Francophone female authors translated in the USA (a completely different book market) between 1990 and 2003 (Sapiro), and c) the situation of Italian female authors translated in Croatia between 1991 and 2020 (Mikšić and Huber), because Italian literature is another romance literature that has occupied an important place in the Croatian literary field for centuries. From the obtained data and analysis, I will in conclusion formulate answers to the questions whether French and Francophone female authors are sufficiently recognized and acknowledged in Croatian culture as representatives of one of the dominant world literatures, and whether there is a positive egalitarian trend in the Croatian literary field that is observed in the world literary field.